Featured Cover. (15th October 2021) - Fan, Chenchen; Lam, James; Xie, Xiaochen
Abstract : The cover image is based on the Research Article Fault estimation for periodic piecewise T‐S fuzzy systems by Chenchen Fan et al., https://doi.org/10.1002/rnc.5733 .